Cross-Border E-Commerce and Urban Entrepreneurial Vitality—A Quasi-Natural Experiment Evidence from China - Yuan, Qigang; Ji, Yongsheng; Zhang, Wei; Lei, Ting (Sustainability, 2024)
Cross-border e-commerce, as a new form of trade driven by digital technology, provides an opportunity to enhance the entrepreneurial vitality of cities. With the help of the comprehensive pilot area for cross-border e-commerce, also called a “quasi-natural” experiment, and using 2010–2020 panel data and Chinese business enterprise registration data for 278 cities in China, this paper examined the impact of cross-border e-commerce on enterprise vitality. The study found that the pilot policy in the comprehensive pilot area promoted the entrepreneurial vitality to increase by about 13.3%, and it remained stable after a series of tests. The heterogeneity analysis shows that the pilot policies in the comprehensive pilot areas have a stronger effect on the promotion of enterprise vitality in the eastern and western regions. At the same time, the pilot policy has expanded the scope of enterprise subjects and plays a more prominent enterprise incentive effect in small and medium-sized cities, cities with low innovation, and small and medium-sized registered enterprises. In addition, the pilot policy stimulates the entrepreneurial vitality of the service industry, but has no significant impact on agriculture and manufacturing. In terms of the influence mechanism, the comprehensive pilot area mainly affects the entrepreneurial vitality by means of optimizing the business environment, reducing the entry cost, promoting the synergistic agglomeration of manufacturing and producer services, and stimulating market demand. The further spatial spillover effect found that the comprehensive pilot area not only improves the entrepreneurial vitality of the pilot cities, but also radiates the enterprise development of neighboring and surrounding cities with similar economic development.